Physical activity level in people with age related white matter changes correlates to better motor performance, lower comorbidity and higher cognitive level - Pettersson, Anna F.; Bäzner, Hansjörg (BMC geriatrics, 2017)
Background: Physical activity plays a pivotal role in the development of disability and may modify the negative effect of vascular risk factors on progression of both cardio and cerebrovascular disorders. The aim of this study was to evaluate the activity level in people with age-related white matter changes as identified on magnetic resonance imaging (MRI) in relation to motor performance, cognition and perceived health. Methods: Data came from the first year follow up of one participating centers of the LADIS study. Fifty one subjects were first enrolled in the study. Complete first year follow up data was available for 41 subjects. Information on comorbidity, physical activity level, physical function, cognition, level of white matter changes and perceived health was collected. Physical activity level was classified with a yes or no question and with the Frenchay Activities Index (FAI). Results: Only 36% of the subjects in this study were physically active according to the yes/no question. 27.5% of the subjects were active according to the FAI score which evaluates the everyday activities. Being active discriminated subjects with better physical function. Subjects active according to the FAI score had a higher cognitive level (p ≤ 0.01), lower comorbidity (p = 0.02) and performed better on all motor function tasks as assessed by walking speed (p ≤ 0.01) and the Short Physical Performance battery (SPPB) (p ≤ 0.01). Conclusions: Being physically active seems to be a long term protective factor. In our study, the majority of subjects with Age Related White Mattter Changes (ARWMC) with no or mild Instrumental Activity of Daily Living (IADL) disability did not attain recommended level of activity at first year follow up. Whether or not increasing physical activity may slow down cognitive decline and lessen development of disability in physically inactive subjects with manifest ARWC remains to be studied. Trial registration: not applicable.